PLANT WATER RELATIONS AND DROUGHT ADAPTATIONS OF SCHIMA WALLICHII AT PHULCHOWKI HILL, NEPAL - Poudyal, K (Scientific World, 2015)
In the central Himalaya, plants are subjected to a prolonged dry period, thus developing moisture stress. Variations in water relations and their response to drought in a Himalayan tree species, Schima wallichii at 1400 m elevation were studied at Phulchowki Hill, Kathmandu, Nepal. To understand the adaptational strategy of this species through which it withstands water stress, different parameters such as soil water potential at 15 (Y15) and 30 (Y30) cm depths, tree water potential at predawn (Ypd) and midday (Ymd), leaf conductance during morning (gw AM) and afternoon (gw PM) and correlation between all these variables were measured from December 1998 to April 2001, except during monsoon months. There was significant variation among months and years in Ypd, Ymd, AM and gwPM. Mean Ypd and Ymd were -0.20 and –0.63 MPa, respectively. The minimum Y value was observed in March 1999, after 4 months of unusually no rainfall. Some patterns of Ypd were related to phenology and leaf damage as Ypd often increased during leafing. Mean gw AM and gw PM were 95 and 75 m molm–2s–1, respectively. Schima wallichii maintained high Y, with low stomatal conductance reflecting its inherent dehydration postponement adaptation.. Scientific World, Vol. 12, No. 12, September 2014, page 79-84